2022
DOI: 10.1017/jns.2022.2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with minimum dietary diversity failure among Indian children

Abstract: Recognising the importance of infant and young child feeding practices during the first 2 years of life, the World Health Organization's Global Nutrition Monitoring Framework developed a minimum dietary diversity (MDD) indicator for feeding children aged 6–23 months. MDD is defined as the consumption of food items from five or more groups out of a total of eight food groups. Food intake from less than five food groups is considered minimum dietary diversity failure (MDDF). Using the nationally representative N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(38 reference statements)
2
6
1
Order By: Relevance
“…Children with older mothers were more likely to have MDD than children with younger-aged mothers, and this finding is in line with the previous study conducted in Bangladesh 40. This could be due to older mother having adequate experience in taking care of their children and being more conscious about their children’s feeding practices which makes a difference and increase the MDD among their children 41 42. We found that children from households with media access, such as watching TV or reading newspapers/magazines were more likely to have MDD than those from the family with no media access.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Children with older mothers were more likely to have MDD than children with younger-aged mothers, and this finding is in line with the previous study conducted in Bangladesh 40. This could be due to older mother having adequate experience in taking care of their children and being more conscious about their children’s feeding practices which makes a difference and increase the MDD among their children 41 42. We found that children from households with media access, such as watching TV or reading newspapers/magazines were more likely to have MDD than those from the family with no media access.…”
Section: Discussionsupporting
confidence: 90%
“…Explanatory variables were grouped into the following categories: maternal and family factors, factors related to media exposure, factors related to health services use, and child factors. Maternal and family factors included the age group of mothers in years,11 15–46 the mother’s and partner’s education level (no education, primary, secondary, higher), mother’s employment (yes, no), partner’s occupation (agriculture, services, others), household wealth status, which was used to calculate the concentration index (CIX) of dietary diversity, was determined to be one of the primary explanatory variables (poorest, poorer, middle, higher, highest) and place of residence (urban, rural). Watching television (TV) and reading newspapers/magazines (yes, no) were also taken into consideration when conducting the decomposition and regression model as factors related to media exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, receiving dietary counseling also facilitates a higher level of diversity among women. Parallel findings have been reported by Rai et al (2022) and Haque et al (2023).…”
Section: Discussionsupporting
confidence: 89%
“…Various studies have been conducted in SA to explore the associated factors of IYCF practices [ 18 , 19 , 20 , 21 , 22 ] and have identified a range of detrimental factors, including but not limited to the place of residence, household wealth status, household income, cultural beliefs, parental education, mother’s age, mother’s occupation, antenatal and postnatal care, child’s age, child’s sex, modes of delivery, place of delivery, and women’s and mother’s exposure to mass media [ 18 , 19 , 20 , 21 , 22 ]. Among all these factors, the role of mother’s education is beneficial to health and nutritional well-being [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%